2001
DOI: 10.21273/hortsci.36.2.365
|View full text |Cite
|
Sign up to set email alerts
|

Heat Tolerance of Kentucky Bluegrass as Affected by Trinexapac-ethyl

Abstract: Heat accumulation during storage of sod may reach lethal temperatures within 4 days, decreasing sod quality. Treatment with trinexapac-ethyl reduces heat accumulation during sod storage. However, heat tolerance of grasses treated with trinexapacethyl has not been documented. Our objectives were to: 1) determine the lethal temperatures for Kentucky bluegrass (Poa pratensis L.); and 2) identify the effect of a single application of trinexapac-ethyl on heat tolerance. Experimental design was a randomized complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…It has been shown to reduce grass clipping yield in multiple grass species including Kentucky bluegrass ( Poa pratensis ), perennial ryegrass, creeping bentgrass and ABG (Ervin & Koski, , ; Kreuser & Soldat, ; Landry & Murphy, ). The chemical TE has been shown to decrease tolerance to heat stress in Kentucky bluegrass (Heckman, Horst, Gaussoin, & Young, ). However, TE has also been shown to play a role in improving heat tolerance when combined with drought stress in creeping bentgrass (McCann & Huang, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to reduce grass clipping yield in multiple grass species including Kentucky bluegrass ( Poa pratensis ), perennial ryegrass, creeping bentgrass and ABG (Ervin & Koski, , ; Kreuser & Soldat, ; Landry & Murphy, ). The chemical TE has been shown to decrease tolerance to heat stress in Kentucky bluegrass (Heckman, Horst, Gaussoin, & Young, ). However, TE has also been shown to play a role in improving heat tolerance when combined with drought stress in creeping bentgrass (McCann & Huang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Heckman et al. () concluded that it could have been due to TE being in the same class as cyclohexanedione, which interrupts lipid synthesis. Effects on lipid synthesis are relevant to the FA results found here.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of PGRs on turfgrass CERs are generally measured on turfgrass canopies rather than single leaves due to the tedious nature of turfgrass leaf area measurements. However, gibberellin‐inhibiting PGRs have been reported to increase turfgrass canopy density through increasing tillering, widening leaf blades, and delaying leaf senescence (Heckman et al, 2001; Ervin and Koski, 2001; Ervin and Koski, 1998; Wiles and Williams, 1985). Therefore, calculation of turfgrass CERs on a ground area basis without taking into account changes in leaf area may not accurately reflect the effects of PGRs on single plant and/or sward CERs.…”
mentioning
confidence: 99%
“…Previous studies with plant growth regulators such as TE have found beneficial effects on plant stress tolerance (Heckman et al, 2001; Zhang et al, 2003; McCann and Huang, 2008; Bian et al, 2009; Xu and Huang, 2010). To our knowledge, our study is the first to examine the combined effects of a plant growth regulator with a fungicide that has plant health benefits under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This ultimately results in plants having reduced height, increased density, and improved canopy characteristics (McCullough et al, 2007; Wherley and Sinclair, 2009). Furthermore, TE has also been implicated in improving the abiotic stress tolerance of turfgrasses (Heckman et al, 2001; Zhang et al, 2003). These effects of TE on abiotic stress tolerance have been studied in creeping bentgrass ( Agrostis stolonifera L.), with the applications of TE improving drought tolerance by maintaining leaf hydration, leaf growth, and photosynthetic parameters (McCann and Huang, 2008), as well as increasing osmotic adjustment (Bian et al, 2009).…”
mentioning
confidence: 99%